Implementasi Progam Pelatihan Anyaman Tas Plastik Untuk Menciptakan Peluang Usaha di Desa Wagir Lor - Nur Mahfud Efendi; Dawam Multazamy Rohmatulloh (Social Science Academic, 2025)
This study explores the implementation of a plastic bag weaving training program as an initiative to generate new business opportunities in Wagir Lor Village, Ngebel District, Ponorogo Regency. The program was motivated by the limited diversity of local micro-enterprises, which have largely centered on agriculture and small-scale traditional crafts. Using a qualitative field research approach, data were collected through observation, interviews, and documentation involving 17 housewives as participants. The results indicate that the participants showed strong enthusiasm, with several producing woven bags of sufficient quality to be sold in the market. They also recognized the potential of this skill to serve as an additional source of household income. Challenges encountered included limited prior experience, time constraints, and difficulties in maintaining weaving consistency. These issues, however, can be addressed through ongoing practice and sustained guidance. The village government expressed its support for developing the program into a community-based micro-enterprise. Overall, the training demonstrates potential not only to promote the creative economy but also to strengthen economic self-reliance and open sustainable business opportunities within the village.